Optimal Oxygen Titration in Patients with Chronic Obstructive Pulmonary Disease: A Role for Automated Oxygen Delivery? - François Lellouche; Jed Lipes; Erwan L’Her (Canadian Respiratory Journal)
Oxygen therapy can be life-saving for patients with chronic obstructive pulmonary disease (COPD) and is the backbone of any acute COPD treatment strategy. Although largely considered to be a benign drug, many publications have highlighted the need to accurately adjust oxygen delivery to avoid both hypoxemia and the problem of hyperoxia-induced hypercapnia. Recent clinical data have shown that the deleterious effects of excess oxygen treatment can not only alter carbon dioxide levels (which has been known for more than 60 years) but can also lead to an increase in mortality. Nevertheless, despite the extensive literature, the risks associated with hyperoxia are often overlooked and published clinical recommendations are largely ignored. This failure in knowledge translation has become increasingly important not only because of the desire to reduce medical error, but in a society with limited health care resources, the economic burden of COPD is such that it cannot afford to make preventable medical mistakes. Recently, novel devices have been developed to automatically adjust oxygen flow rates to maintain stable oxygen saturations. These closed-loop oxygen delivery systems have the potential to reduce medical error, improve morbidity and mortality, and reduce health care costs. Preliminary data in this field are promising and will require a significant amount of research in the coming years to determine the precise indications for these systems. The importance of appropriate oxygen dosing and the current literature regarding novel oxygen delivery systems are reviewed.